Basal Histamine H-4 Receptor Activation: Agonist Mimicry by the Diphenylalanine Motif - Wifling, David; Pfleger, Christopher; Kaindl, Jonas; Ibrahim, Passainte; Kling, Ralf; Buschauert, Armin; Gohlke, Holger; Clark, Timothy (Chemistry - A European Journal, 2019)
Histamine H-4 receptor (H4R) orthologues are G-protein-coupled receptors (GPCRs) that exhibit species-dependent basal activity. In contrast to the basally inactive mouse H4R (mH(4)R), human H4R (hH(4)R) shows a high degree of basal activity. We have performed long-timescale molecular dynamics simulations and rigidity analyses on wild-type hH(4)R, the experimentally characterized hH(4)R variants S179M, F169V, F169V+S179M, F168A, and on mH(4)R to investigate the molecular nature of the differential basal activity. H4R variant-dependent differences between essential motifs of GPCR activation and structural stabilities correlate with experimentally determined basal activities and provide a molecular explanation for the differences in basal activation. Strikingly, during the MD simulations, F169(45.55) dips into the orthosteric binding pocket only in the case of hH(4)R, thus adopting the role of an agonist and contributing to the stabilization of the active state. The results shed new light on the molecular mechanism of basal H4R activation that are of importance for other GPCRs.
CRIS-Team WoS Importer:2019-10-25